2021
DOI: 10.1097/fjc.0000000000001136
|View full text |Cite
|
Sign up to set email alerts
|

Combined Usage of Trimetazidine With 3-Bromopyruvate May Lead to Cardiotoxicity by Activating Oxidative Stress and Apoptosis in Rats

Abstract: The energy used by the heart is generated mainly by the metabolism of fatty acids and glucose. Trimetazidine (TMZ) inhibits fatty acid metabolism and is used for the treatment of heart diseases such as heart failure. 3-Bromopyruvate (3-BrPA) can suppress glucose metabolism, and it is considered a promising candidate agent for tumor therapy. Because TMZ and 3-BrPA can separately inhibit the 2 main cardiac energy sources, it is necessary to investigate the effects of 3-BrPA combined with TMZ on the heart. Forty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, increased fatty acid oxidation caused by acetyl‐CoA carboxylase 2 (ACC2) knockout can inhibit the development of cardiac hypertrophy (Choi et al, 2016). On the other hand, some fatty acid oxidation inhibitors (trimetazidine, etomoxir, perhexiline) showed beneficial effects on cardiac efficiency and have been used to treat heart failure in clinics (George et al, 2016; Nabben et al, 2014; Zheng et al, 2021). Notably, the beneficial effect of fatty acid oxidation inhibitors was accompanied by an increased glucose oxidation level, which has been regarded as the biggest contributor against heart failure (Lopaschuk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increased fatty acid oxidation caused by acetyl‐CoA carboxylase 2 (ACC2) knockout can inhibit the development of cardiac hypertrophy (Choi et al, 2016). On the other hand, some fatty acid oxidation inhibitors (trimetazidine, etomoxir, perhexiline) showed beneficial effects on cardiac efficiency and have been used to treat heart failure in clinics (George et al, 2016; Nabben et al, 2014; Zheng et al, 2021). Notably, the beneficial effect of fatty acid oxidation inhibitors was accompanied by an increased glucose oxidation level, which has been regarded as the biggest contributor against heart failure (Lopaschuk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The hotspots of cell death in cardiovascular eld principally focus on apoptosis, pyroptosis, mitochondrial-mediated cell death, autophagy, and ferroptosis [16]. It has been indicated that TMZ is apt to restrain apoptosis in ischemia/reperfusion (I/R) and diabetic cardiomyopathy models [17][18][19]. And it can also affect pyroptosis by targeting Gasdermin D (GSDMD) and facilitating neutrophil migration [20,21].…”
Section: Introductionmentioning
confidence: 99%